Lattice Structure Optimization Targeting to Enhance the Thermal Performance of An Injection Mold - Zereg Alaeddine; Bouzaher Mohamed Taher; Bassir David; Lebaal Nadhir (E3S Web of Conferences)
The thermal performance of injection molds is critical for achieving high manufacturing efficiency and product quality. This study explores the optimization of lattice structures to enhance heat transfer and cooling effectiveness in injection molds. Two lattice configurations aligned and offset were investigated using computational fluid dynamics in COMSOL Multiphysics, with a focus on evaluating both heat flux and pressure drop characteristics. The offset configuration, which demonstrated approximately 12% higher heat flux while maintaining an acceptable pressure drop, was identified as the optimal design for superior heat dissipation. An optimization framework, integrating design of experiments and surrogate modeling, was employed to determine the lattice parameters that maximize thermal performance while preserving structural stability. These findings underscore the potential of the offset lattice configuration to reduce cycle times and improve product quality, thereby advancing more efficient and sustainable injection molding practices.